2005
DOI: 10.1074/jbc.m500805200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Pyridoxal Kinase in Complex with Roscovitine and Derivatives

Abstract: Pyridoxal kinase (PDXK) catalyzes the phosphorylation of pyridoxal, pyridoxamine, and pyridoxine in the presence of ATP and Zn 2؉ . This constitutes an essential step in the synthesis of pyridoxal 5-phosphate (PLP), the active form of vitamin B 6 , a cofactor for over 140 enzymes. (R)-Roscovitine (CYC202, Seliciclib) is a relatively selective inhibitor of cyclin-dependent kinases (CDKs), currently evaluated for the treatment of cancers, neurodegenerative disorders, renal diseases, and several viral infections.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 38 publications
6
71
0
Order By: Relevance
“…Preclinical toxicology studies with 28 days treatment in rodents reported anaemia, leucocytosis, bone marrow hyperplasia, polydipsia, polyuria and gastric ulceration. Preclinical data indicated that exposure to seliciclib in the concentration range 7.9 -30.2 mM over a 24-h period could achieve clinically relevant biological effects (De la Motte and Gianella-Borradori, 2004;Whittaker et al, 2004;Tang et al, 2005). In vivo studies also indicated that a single dose of 500 mg kg À1 (2750 mg m À2 of mouse body surface area) achieved levels of Z10 mM for 24 h .…”
Section: Discussionmentioning
confidence: 90%
“…Preclinical toxicology studies with 28 days treatment in rodents reported anaemia, leucocytosis, bone marrow hyperplasia, polydipsia, polyuria and gastric ulceration. Preclinical data indicated that exposure to seliciclib in the concentration range 7.9 -30.2 mM over a 24-h period could achieve clinically relevant biological effects (De la Motte and Gianella-Borradori, 2004;Whittaker et al, 2004;Tang et al, 2005). In vivo studies also indicated that a single dose of 500 mg kg À1 (2750 mg m À2 of mouse body surface area) achieved levels of Z10 mM for 24 h .…”
Section: Discussionmentioning
confidence: 90%
“…Chemistry (R)-roscovitine was synthesized as described previously (12,26) and kindly provided by Dr. Hervé Galons and Nassima Oumata (Université René Descartes).…”
Section: Methodsmentioning
confidence: 99%
“…Its selectivity has been extensively studied using either panels of purified kinases (z152 kinases tested; refs. 23 -25), affinity chromatography on immobilized roscovitine (25,26), a quantitative competition assay (27), and a yeast three-hybrid screen (28). Altogether, these methods have provided a rather precise view on the targets of (R)-roscovitine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mammalian PLKs have been successfully expressed in Escherichia coli and the expressed recombinant proteins exhibit the same biochemical characteristics as those of the native protein purified from various mammalian tissues (Gao et al, 1998;Lee et al, 2000;Di Salvo et al, 2004). Recently, the three-dimensional structures of PLKs from bacteria and mammals, alone and in complex with various ligands were determined, providing a better understanding of the catalytic mechanism of PLK (Li et al, 2002(Li et al, , 2004Safo et al, 2004Safo et al, , 2006Tang et al, 2005;Cao et al, 2006). The active sites are structurally very similar among members of the ribokinase superfamily .…”
Section: Introductionmentioning
confidence: 99%